Enhancement of phenolics and antioxidant activity via heat assisted extraction from Moringa oleifera using response surface methodology and its potential bioactive constituents - Kamarudin, 'Ammar Akram; Saad, Norazalina; Sayuti, Nor Hafiza; Ab Razak, Nor Asma; Mohd Esa, Norhaizan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Introduction: Moringa oleifera Lam. is a miracle tree that has been widely utilised in folklore medicine due to its immense amount of phenolic constituents that could treat various ailments. Different techniques have been implemented to extract the phenolic but the parameters may not be optimised to further enhance the amount of phenolic extracted. Thus, the work aimed to enhance phenolic content and antioxidant activity of M. oleifera through RSM methodology, which is rapid and convenience. Methods: At first, antioxidant activity of different parts of M. oleifera (leaves, stem, pod and seed) were investigated. The plant part with the highest antioxidant activity was selected for the optimisation of extraction condition using RSM. In RSM, temperature (XA), extraction time (XB) and solid-liquid ratio (XC) were employed to study the effects on yield, total phenolics, flavonoids and antioxidant activity. Then, the optimum extraction condition obtained via RSM was utilised in LC-MS and HPLC analysis to determine the potential bioactive constituents. Results: The leaves of M. oleifera displayed the highest antioxidant activity as compared to other plant parts. The optimum extraction condition obtained for the leaves extract was: temperature (XA): 82°C, extraction time (XB): 48 min and solid-liquid ratio (XC): 1:30 g/mL (w/v). Meanwhile, LC-MS revealed the presence of gallic acid, chlorogenic acid, quercetin, kaempferol and 3-O-glucoside kaempferol. HPLC analysis detected six compounds; gallic acid, epicatechin gallate, chlorogenic acid, myricetin, quercetin and kaempferol. Conclusion: The optimisation are promising to improve yield and antioxidant activity in M. oleifera as compared to non-conventional extractions.